A magnesium-based desulfurization and denitration catalyst, preparation method and application thereof

By developing a magnesium-based desulfurization and denitrification catalyst, the problems of low efficiency and high cost in industrial flue gas treatment have been solved, and efficient and low-cost flue gas purification effect has been achieved.

CN119771389APending Publication Date: 2025-04-08ZHONGKE DIPU (JIANGYIN) PURIFICATION EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993443.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing industrial flue gas treatment technology has problems such as serious equipment corrosion, large area, high investment and operation costs, as well as poor effectiveness and service life of desulfurization and denitrifying agents.

Method used

A magnesium-based desulfurization and denitrification catalyst was developed to prepare a catalyst with high desulfurization and denitrification efficiency by mixing a magnesium-based material with a binder, a pore reamer and an auxiliary agent, and molding and drying.

Benefits of technology

Under high airspeed conditions, magnesium-based catalysts can maintain high desulfurization and denitrification efficiency, the removal efficiency of SO2 reaches more than 80%, and the removal efficiency of NOx reaches more than 85%, which reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a magnesium-based desulfurization and denitrification catalyst, a preparation method and application thereof, comprising the following raw materials in parts by weight: 100 parts of magnesium-based material; 1 to 20 parts of binder; 0 to 20 parts of pore expander; 0 to 20 parts of auxiliary agent; 10 to 90 parts of water; the binder is one or more of gypsum, pseudo-boehmite, methyl cellulose, sodium aluminate and fly ash. The results of the embodiment show that at room temperature and air velocity of 1000 to 8000 h ‑1 Under the conditions of the present invention, the magnesium-based composite material has a SO2 content of 4000-7000 mg / m 3 When the removal efficiency of SO2 can reach more than 80%; when the removal efficiency of NO x The content is 100~200mg / m 3 When NO x The removal efficiency can reach over 85%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of desulfurization and denitration, and in particular relates to a magnesium-based desulfurization and denitration catalyst, a preparation method and application thereof. Background Art

[0002] Driven by the "dual carbon" goal, industrial flue gas treatment has become an important challenge facing Chinese companies. China burns a large amount of fossil fuels every year, emitting a large amount of industrial flue gas. The sulfur dioxide (SO 2 ) and nitrogen oxides (NO x ) not only seriously pollutes the air, but also has a negative impact on the ecological environment. In response to the problems of severe equipment corrosion, large floor space, high investment and operating costs, and poor desulfurization and denitrification agent effects and service life in the field of industrial flue gas treatment, we have proposed a new solid desulfurization and denitrification integrated (STD) technology concept, aiming to improve the efficiency of industrial flue gas resource utilization technology and reduce emissions. This technology is expected to become an effective way to solve industry problems.

[0003] Therefore, the research and development of magnesium-based composite materials for desulfurization and denitrification is not only of great significance, but also has great regional advantages. Summary of the invention

[0004] The purpose of the present invention is to provide a magnesium-based desulfurization and denitration catalyst, a preparation method and application thereof. The magnesium-based desulfurization and denitration catalyst of the present invention still has high desulfurization efficiency and denitration efficiency at high space velocity.

[0005] The present invention provides a magnesium-based desulfurization and denitration catalyst, comprising the following preparation raw materials in parts by weight:

[0006] 100 parts of magnesium-based materials;

[0007] 1 to 20 parts of binder;

[0008] Pore ​​expanding agent 0-20 parts;

[0009] Additives 0-20 parts;

[0010] 10-90 parts of water;

[0011] The binder is one or more of gypsum, pseudo-boehmite, methyl cellulose, sodium aluminate and fly ash.

[0012] Preferably, the magnesium-based material includes one or more of magnesium oxide, magnesium hydroxide, magnesium carbonate and magnesium salt.

[0013] Preferably, the pore expanding agent comprises ethanol and / or urea.

[0014] Preferably, the auxiliary agent comprises alkaline earth metal oxide and / or alkali metal hydroxide.

[0015] Preferably, the alkaline earth metal oxide includes one or more of aluminum oxide, manganese oxide, manganese dioxide and iron oxide; and the alkali metal hydroxide includes sodium hydroxide.

[0016] The present invention provides a method for preparing the magnesium-based desulfurization and denitrification catalyst as described above, comprising the following steps:

[0017] A) mixing a magnesium-based material with a binder to obtain a first mixture;

[0018] B) mixing the first mixture with a pore-enlarging agent and an auxiliary agent to obtain a second mixture;

[0019] C) mixing the second mixture with water to obtain a third mixture;

[0020] D) forming and drying the third mixture to obtain a magnesium-based desulfurization and denitration catalyst.

[0021] Preferably, the drying temperature in step D) is 80-120° C., and the drying time in step D) is 8-20 h.

[0022] The present invention provides the use of the magnesium-based desulfurization and denitrification catalyst as described above in flue gas desulfurization and denitrification.

[0023] Preferably, the SO in the flue gas 2 The content is 4000~7000mg / m 3 , NO x The content is 100~300mg / m 3 .

[0024] Preferably, the air velocity of the flue gas desulfurization and denitrification is 1000-8000h -1 .

[0025] The present invention provides a magnesium-based desulfurization and denitrification catalyst, comprising the following raw materials in parts by weight: 100 parts of magnesium-based material; 1 to 20 parts of a binder; 0 to 20 parts of a pore expander; 0 to 20 parts of an auxiliary agent; and 10 to 90 parts of water; wherein the binder is one or more of gypsum, pseudo-boehmite, methyl cellulose, sodium aluminate and fly ash.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention increases the specific surface area of ​​the magnesium-based composite material by adding a certain amount of pore-enlarging agent, which is beneficial to NO x and SO 2 Entering the internal pores of the magnesium-based composite material, increasing the NO x and SO 2The contact area with magnesium-based materials increases the efficiency of desulfurization and denitrification.

[0028] (2) The binder added in the present invention has low cost, which reduces the cost of the magnesium-based composite material and reduces the investment in the corresponding desulfurization process, thus having certain cost advantages.

[0029] (3) The present invention further improves the desulfurization and denitrification capabilities of the magnesium-based composite material by using a specific type of additive.

[0030] The results of the embodiment show that at room temperature and air velocity of 1000-8000h -1 Under the conditions of SO 2 The content is 4000~7000mg / m 3 When SO 2 The removal efficiency of NO can reach more than 80%. x The content is 100~200mg / m 3 When NO x The removal efficiency can reach over 85%. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0032] Figure 1 is the NO of Example 1, Example 2 and Example 5 at different temperatures x Removal comparison chart;

[0033] Figure 2 is the NO of Comparative Examples 1 to 6 at different temperatures x Removal comparison chart;

[0034] Figure 3 is the SO of Example 1, Example 2 and Example 5 at different temperatures 2 Removal comparison chart;

[0035] Figure 4 The SO of Comparative Examples 1 to 6 at different temperatures 2 Removal comparison chart;

[0036] Figure 5 is the NO of Example 1, Comparative Example 1 and Comparative Example 2 at different temperatures x Removal comparison chart;

[0037] Figure 6The SO of Example 1, Comparative Example 1 and Comparative Example 2 at different temperatures 2 Removal comparison chart. DETAILED DESCRIPTION

[0038] The present invention provides a magnesium-based desulfurization and denitration catalyst, comprising the following raw materials in parts by weight:

[0039] 100 parts of magnesium-based materials;

[0040] 1 to 20 parts of binder;

[0041] Pore ​​expanding agent 0-20 parts;

[0042] Additives 0-20 parts;

[0043] 10-90 parts of water;

[0044] The binder is one or more of gypsum, pseudo-boehmite, methyl cellulose, sodium aluminate and fly ash.

[0045] The raw materials for preparing the magnesium-based composite material provided by the present invention include 100 parts of magnesium-based materials, and the magnesium-based materials preferably include one or more of magnesium oxide, magnesium hydroxide, magnesium carbonate and magnesium salts. In the present invention, the magnesium-based material is preferably magnesium oxide; in the present invention, the magnesium-based material is used as an active component for desulfurization and denitrification.

[0046] In the present invention, based on the weight of the magnesium-based material, the raw materials for preparing the magnesium-based composite material provided by the present invention include 1 to 20 parts of a binder, preferably 5 to 15 parts, such as 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, preferably a range value with any of the above values ​​as the upper or lower limit. In the present invention, the binder is one or more of gypsum, pseudo-boehmite, methyl cellulose, sodium aluminate and fly ash. The present invention enhances the mechanical strength and water resistance of the magnesium-based composite material by adjusting the type and amount of the binder, so that it is not easy to pulverize in the presence of water vapor, so that it is suitable for desulfurization and denitrification under complex working conditions. If pulverization occurs, the pores of the magnesium-based composite material will collapse, affecting the desulfurization effect. And the cost of the magnesium-based composite material is reduced, so that the corresponding desulfurization process investment is small, and it has certain cost advantages.

[0047] In the present invention, based on the weight proportion of the magnesium-based material, the raw materials for preparing the magnesium-based composite material provided by the present invention preferably also include 0 to 20 parts of a pore expander, and more preferably 5 to 15 parts, such as 0 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, preferably a range value with any of the above values ​​as the upper or lower limit. In the present invention, the pore expander preferably includes ethanol or urea. The ethanol in the pore expander of the present invention will evaporate during the preparation of the magnesium-based composite material to form a pore structure; the urea will decompose to form a pore structure. The present invention enables the magnesium-based composite material to have suitable pores by adjusting the amount and type of the pore expander, so that NO x and SO 2 Entering into the interior of the magnesium-based composite material, the contact area between the pollutants and the magnesium-based material is increased, thereby improving the efficiency of desulfurization and denitrification.

[0048] In the present invention, based on the weight percentage of the magnesium-based material, the raw materials for preparing the magnesium-based composite material provided by the present invention also include 0 to 20 parts of auxiliary agents, and more preferably 5 to 15 parts, such as 0 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, preferably a range value with any of the above values ​​as the upper or lower limit. In the present invention, the auxiliary agent preferably includes alkaline earth metal oxides and / or alkali metal hydroxides; the metal oxide preferably includes one or more of aluminum oxide, manganese oxide, manganese dioxide and iron oxide; the alkali metal hydroxide preferably includes sodium hydroxide. The present invention further improves the resistance of the magnesium-based composite material to NO by selecting the type of auxiliary agent. x and SO 2 removal ability.

[0049] In the present invention, based on the weight percentage of the magnesium-based material, the raw materials for preparing the magnesium-based composite material provided by the present invention also include 10 to 90 parts of water, more preferably 20 to 80 parts, such as 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, preferably a range value with any of the above values ​​as the upper or lower limit.

[0050] The present invention provides a method for preparing the magnesium-based desulfurization and denitrification catalyst as described above, comprising the following steps:

[0051] A) mixing a magnesium-based material with a binder to obtain a first mixture;

[0052] B) mixing the first mixture with a pore-enlarging agent and an auxiliary agent to obtain a second mixture;

[0053] C) mixing the second mixture with water to obtain a third mixture;

[0054] D) forming and drying the third mixture to obtain a magnesium-based desulfurization and denitration catalyst.

[0055] In the present invention, the types and amounts of the magnesium-based material, binder, pore expander, additive and water are consistent with the types and amounts of the magnesium-based material, binder, pore expander, additive and water described above, and the present invention will not be repeated here.

[0056] In the present invention, the mixing operations in steps A), B) and C) are preferably carried out in a planetary mixer. The mixing in the above order can make the prepared raw materials mixed evenly, thereby improving the mechanical strength of the magnesium-based composite material, and further ensuring the desulfurization and denitrification effects.

[0057] In the present invention, the molding is preferably extrusion molding, and the extrusion molding method commonly used in the art can be adopted, which will not be described in detail in the present invention.

[0058] In the present invention, the drying temperature is preferably 80-120°C, more preferably 90-110°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, preferably a range value with any of the above values ​​as the upper or lower limit; the drying time is preferably 8-20 hours, more preferably 10-15 hours.

[0059] The present invention also requires airing before drying. In the present invention, the airing time is 2 to 4 hours. The airing is performed at room temperature.

[0060] The present invention also provides an application of the above-mentioned magnesium-based desulfurization and denitrification catalyst in flue gas desulfurization and denitrification. The magnesium-based desulfurization and denitrification catalyst in the present invention is used as a desulfurization and denitrification agent in flue gas purification and emission.

[0061] In the present invention, the flue gas is preferably the flue gas from the calcination section of an aluminum carbon enterprise. 2 The content is 4000~7000mg / m 3 ; NO x The content is 100~300mg / m 3 ; The moisture content is preferably 0 to 4788 g / m 3 The application method is: the magnesium-based composite material is loaded into a desulfurization and denitrification device, the temperature of the flue gas is generally 130-180°C; the air velocity of the desulfurization and denitrification is preferably 1000-8000h -1 The magnesium-based desulfurization and denitrification catalyst of the present invention has excellent desulfurization and denitrification effects in flue gas purification, especially at high air velocity such as 7000h -1The denitrification effect under the conditions is significantly improved compared with the existing technology.

[0062] The present invention provides a magnesium-based desulfurization and denitrification catalyst, comprising the following raw materials in parts by weight: 100 parts of magnesium-based material; 1 to 20 parts of a binder; 0 to 20 parts of a pore expander; 0 to 20 parts of an auxiliary agent; and 10 to 90 parts of water; wherein the binder is one or more of gypsum, pseudo-boehmite, methyl cellulose, sodium aluminate and fly ash.

[0063] Compared with the prior art, the present invention has the following beneficial effects:

[0064] (1) The present invention increases the specific surface area of ​​the magnesium-based composite material by adding a certain amount of pore-enlarging agent, which is beneficial to NO x and SO 2 Entering the internal pores of the magnesium-based composite material, increasing the NO x and SO 2 The contact area with magnesium-based materials increases the efficiency of desulfurization and denitrification.

[0065] (2) The binder added in the present invention has low cost, which reduces the cost of the magnesium-based composite material and reduces the investment in the corresponding desulfurization process, thus having certain cost advantages.

[0066] (3) The present invention further improves the desulfurization and denitrification capabilities of the magnesium-based composite material by using a specific type of additive.

[0067] The results of the embodiment show that at room temperature and air velocity of 1000-8000h -1 Under the conditions of SO 2 The content is 4000~7000mg / m 3 When SO 2 The removal efficiency of NO can reach more than 80%. x The content is 100~200mg / m 3 When NO x The removal efficiency can reach over 85%.

[0068] In order to further illustrate the present invention, a magnesium-based desulfurization and denitrification catalyst provided by the present invention, its preparation method and application are described in detail below in combination with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0069] Example 1

[0070] 9.5 g of magnesium oxide and 0.5 g of fly ash were mixed and stirred for 3 min, then mixed with 2 mL of ethanol and 2 g of aluminum oxide, and 20 mL of deionized water was added and stirred. The obtained mixture was extruded into strips, dried for 3 h, and then dried at 80 ° C for 8 h. After being cut into small sections, a magnesium-based composite material was obtained, which was recorded as A-1 magnesium-based composite material.

[0071] Example 2

[0072] Under laboratory conditions, 49.5 g of magnesium oxide and 0.5 g of pseudo-boehmite were mixed and stirred for 3 minutes, then mixed with 1 mL of ethanol and 2 g of sodium hydroxide, and 20 mL of deionized water was added and stirred. The resulting mixture was extruded into strips, dried for 3 hours, and then dried at 100°C for 8 hours. After being cut into small sections, a magnesium-based composite material was obtained, which was recorded as A-2 magnesium-based composite material.

[0073] Example 3

[0074] Under laboratory conditions, 49.5 g of magnesium oxide and 0.5 g of sodium aluminate were mixed and stirred for 3 minutes. The mixture was then mixed with 1.5 g of urea and 2 g of manganese dioxide, and 20 mL of deionized water was added and stirred. The resulting mixture was extruded into strips, dried for 3 hours, and then dried at 120°C for 8 hours. The magnesium-based composite material was obtained after being cut into small sections, which was recorded as A-3 magnesium-based composite material.

[0075] Example 4

[0076] Under laboratory conditions, 49.5 g of magnesium oxide and 0.5 g of methyl cellulose were mixed and stirred for 3 minutes. The mixture was then mixed with 2.5 mL of ethanol and 1.5 g of iron oxide, and 20 mL of deionized water was added and stirred. The resulting mixture was extruded into strips, dried for 3 hours, and then dried at 80°C for 8 hours. The magnesium-based composite material was obtained after being cut into small sections, which was recorded as A-4 magnesium-based composite material.

[0077] Example 5

[0078] Under laboratory conditions, 49.5 g of magnesium oxide and 0.5 g of sodium aluminate were mixed and stirred for 3 minutes. The mixture was then mixed with 1.5 mL of ethanol and 1.5 g of sodium hydroxide, and 20 mL of deionized water was added and stirred. The resulting mixture was extruded, dried for 3 hours, and then dried at 90°C for 8 hours. The magnesium-based composite material was obtained after being cut into small sections, which was recorded as A-5 magnesium-based composite material.

[0079] Comparative Example 1

[0080] A magnesium-based composite material was prepared according to the method in Example 1, except that no pore-enlarging agent (ethanol) and auxiliary agent (aluminum oxide) were added in Comparative Example 1. The composite material prepared was recorded as B-1 magnesium-based composite material.

[0081] Comparative Example 2

[0082] A magnesium-based composite material was prepared according to the method in Example 1, except that no auxiliary agent (aluminum oxide) was added in Comparative Example 2. The composite material prepared was recorded as B-2 magnesium-based composite material.

[0083] Comparative Example 3

[0084] A magnesium-based composite material was prepared according to the method in Example 2, except that no pore-enlarging agent (ethanol) was added in Comparative Example 3. The composite material prepared was recorded as B-3 magnesium-based composite material.

[0085] Comparative Example 4

[0086] A magnesium-based composite material was prepared according to the method in Example 3, except that no auxiliary agent (manganese dioxide) was added in Comparative Example 4. The composite material prepared was recorded as B-4 magnesium-based composite material.

[0087] Comparative Example 5

[0088] A magnesium-based composite material was prepared according to the method in Example 4, except that no pore-enlarging agent (ethanol) and auxiliary agent (iron oxide) were added in Comparative Example 5. The composite material prepared was recorded as B-5 magnesium-based composite material.

[0089] Comparative Example 6

[0090] A magnesium-based composite material was prepared according to the method in Example 5, except that no auxiliary agent (sodium hydroxide) was added in Comparative Example 6. The composite material prepared was recorded as B-6 magnesium-based composite material.

[0091] The magnesium-based composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were subjected to strength testing using a particle size strength testing machine: the magnesium-based composite materials were selected, cut into small cylinders, and subjected to strength testing. Each sample was measured ten times, and the average value was selected and counted. The experimental results are shown in Table 1.

[0092] Table 1 Strength test results of magnesium-based composite materials of Examples 1 to 5 and Comparative Examples 1 to 6

[0093] Magnesium-based composites A-1 A-2 A-3 A-4 A-5 B-1 B-2 B-3 B-4 B-5 B-6 Strength / N 73.2 62.7 99.0 32.7 57.0 87.1 42.6 97.9 51.8 91.3 53.4

[0094] As shown in Table 1, A-3 and B-3 have higher strength, better wear resistance and higher compressive strength, and are suitable for flue gas removal in coal-fired power plants, industrial boilers, industrial kilns and petrochemical industries. However, A-4 has relatively poor strength, which may be due to the presence of iron oxide, so it will not be tested in subsequent experiments.

[0095] The magnesium-based composite materials of Examples 1 to 3 and Comparative Examples 1 to 6 were soaked in water at room temperature 25° C. for 168 hours, and then dried to test their strength. The experimental results are shown in Table 2.

[0096] Table 2 Strength test results of magnesium-based composite materials after soaking in water of Examples 1 to 3 and Comparative Examples 1 to 6

[0097]

[0098]

[0099] It can be seen from Table 2 that the hardness of A-1, A-2, B-3, B-4, B-5 ​​and B-6 does not change much and can be used as desulfurizers. After soaking in water, the hardness of A-3 decreases significantly. Analysis shows that this may be caused by the pore-expanding agent urea, which can easily cause the desulfurizer structure to be unstable and the strength to deteriorate. It is not suitable for use in an environment with a high water content, so it is not added to the subsequent flue gas desulfurization and denitrification tests.

[0100] Example 1, Example 2, Example 5 and Comparative Examples 1 to 6 respectively use 20 cm 3 The magnesium-based composite material is used as a desulfurization and denitrification agent. In the laboratory, the flue gas is filled into a cylinder according to the simulated factory proportion. The flue gas composition is shown in Table 3.

[0101] Table 3 Smoke composition

[0102] Components content <![CDATA[CO 2 ]]> 10% <![CDATA[SO 2 ]]> <![CDATA[4000mg / m 3 ]]> <![CDATA[NO x ]]> <![CDATA[300mg / m 3 ]]> Air balance

[0103] The flue gas is connected to a desulfurization and denitration reaction device with temperature control, and the tail gas treated by the desulfurization and denitration device is discharged into the air. A Testo 350 flue gas analyzer is connected to the tail gas outlet for measurement. Different desulfurization and denitration agents are sequentially used in the desulfurization and denitration devices for desulfurization and denitration. The magnesium-based composite materials NO of Example 1, Example 2, Example 5 and Comparative Examples 1 to 6 are used at different temperatures. x Removal efficiency and SO 2 The removal efficiency results are shown in Table 4 and Figures 1 to 6 shown.

[0104] Table 4 Desulfurization and denitrification efficiency of different catalysts at different temperatures (7000h -1 )

[0105]

[0106]

[0107] It can be seen from the test results in the above table that the desulfurization and denitrification rates of the embodiments are generally better than those of the comparative examples. It can be concluded that the magnesium-based composite material in the present invention is particularly suitable for the treatment of high-flow rate or low-concentration sulfur- and nitrogen-containing gases. For example, under high air velocity conditions, the magnesium-based composite material in the present invention can still maintain a relatively high desulfurization and denitrification efficiency.

[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A magnesium-based desulfurization and denitrification catalyst, comprising the following raw materials in parts by weight: 100 parts of magnesium-based materials; 1 to 20 parts of binder; Pore ​​expanding agent 0-20 parts; Additives 0-20 parts; 10-90 parts of water; The binder is one or more of gypsum, pseudo-boehmite, methyl cellulose, sodium aluminate and fly ash.

2. The magnesium-based desulfurization and denitrification catalyst according to claim 1, characterized in that: The magnesium-based material includes one or more of magnesium oxide, magnesium hydroxide, magnesium carbonate and magnesium salt.

3. The magnesium-based desulfurization and denitrification catalyst according to claim 1, characterized in that: The pore expanding agent includes ethanol and / or urea.

4. The magnesium-based desulfurization and denitrification catalyst according to claim 1, characterized in that: The auxiliary agent includes alkaline earth metal oxides and / or alkali metal hydroxides.

5. The magnesium-based desulfurization and denitrification catalyst according to claim 1, characterized in that: The alkaline earth metal oxide includes one or more of aluminum oxide, manganese oxide, manganese dioxide and iron oxide; the alkali metal hydroxide includes sodium hydroxide.

6. A method for preparing a magnesium-based desulfurization and denitrification catalyst as claimed in claim 1, comprising the following steps: A) mixing a magnesium-based material with a binder to obtain a first mixture; B) mixing the first mixture with a pore-enlarging agent and an auxiliary agent to obtain a second mixture; C) mixing the second mixture with water to obtain a third mixture; D) forming and drying the third mixture to obtain a magnesium-based desulfurization and denitration catalyst.

7. The preparation method according to claim 6, characterized in that: The drying temperature in the step D) is 80 to 120° C., and the drying time in the step D) is 8 to 20 hours.

8. Use of the magnesium-based desulfurization and denitrification catalyst as claimed in claim 1 in flue gas desulfurization and denitrification.

9. The use according to claim 8, characterized in that: The content of SO2 in the flue gas is 4000-7000 mg / m 3 , NO x The content is 100~300mg / m 3 .

10. The use according to claim 9, characterized in that: The space velocity of flue gas desulfurization and denitrification is 1000~8000h -1 .